Inovasi Pembelajaran Pendidikan Agama Islam di Era Revolusi Industri 4.0 Melalui Media Massive Open Online Course (MOOC) - Yordan Nafa; Moh Sutomo; Moh Sahlan (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2021)
This article discusses Islamic Religious Education (PAI) in the digital era, Massive Open Online Course (MOOC) media as a learning innovation that is more modern, adaptive, and aligned with the independent learning curriculum. The Independent learning approach help learners broaden their horizons and improve their abilities based on their separate learning experiences. The success and quality of learning, especially Islamic Religious Education, can be supported by the course design contained in the MOOC. The advantages of flexible and collaborative MOOC learning media can be shared between universities and are expected to improve the quality of Islamic Religious Education in Indonesia. The research method uses a qualitative descriptive approach to explore Islamic Religious Education innovations in the Industrial Revolution 4.0 era through Massive Open Online Course (MOOC) media. The final result is the MOOC learning media as an innovation for Islamic Religious Education which is adaptively prepared in Islamic Higher Education and is aligned with the independent learning curriculum.